2018
DOI: 10.18632/oncotarget.25724
|View full text |Cite
|
Sign up to set email alerts
|

Loss of KIBRA function activates EGFR signaling by inducing AREG

Abstract: The Hippo signaling pathway is a central regulator of organ size, tissue homeostasis, and tumorigenesis. KIBRA is a member of the WW domain-containing protein family and has recently been reported to be an upstream protein in the Hippo signaling pathway. However, the clinical significance of KIBRA deregulation and the underlying mechanisms by which KIBRA regulates breast cancer (BC) initiation and progression remain poorly understood. Here, we report that KIBRA knockdown in mammary epithelial cells induced epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Hence, the reduced expression of Hippo core kinases in the +DDR/+COL1 HT1080 tumours may underlie the ability of these tumours to display accelerated growth. Consistent with the tumour suppressive role of the Hippo pathway, we found that KIBRA, an upstream regulator of the Hippo pathway, and also considered a tumour suppressor [150][151][152][153] , was significantly downregulated in +DDR2/+COL1 but not in +DDR1b/+COL1 tumours. This suggests that KIBRA may be a major target of DDR2 signalling in response to collagen in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, the reduced expression of Hippo core kinases in the +DDR/+COL1 HT1080 tumours may underlie the ability of these tumours to display accelerated growth. Consistent with the tumour suppressive role of the Hippo pathway, we found that KIBRA, an upstream regulator of the Hippo pathway, and also considered a tumour suppressor [150][151][152][153] , was significantly downregulated in +DDR2/+COL1 but not in +DDR1b/+COL1 tumours. This suggests that KIBRA may be a major target of DDR2 signalling in response to collagen in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Loss of WWC1 function could also induce EMT and promote mammary epithelial cell transformation, whereas WWC1 overexpression was found to suppress head and neck squamous cell carcinoma cells in forming colony and oncosphere in soft agar [37]. Based on the findings, WWC1 was considered a potential tumor suppressor [38]. A recent study confirmed that WWC1 could inhibit breast tumor metastasis both in vitro and in vivo [6].…”
Section: Discussionmentioning
confidence: 99%
“…By their WW domains, kidney and brain protein (KIBRA) is bound to Merlin, which is also known as neurofibromin 2 (NF2). Subsequently, the combination of KIBRA and Merlin recruits LATS1/2 to the cell membrane [ 41 43 ]. Meanwhile, the WW domain of the KIBRA binding to SAV results in the form of KIBRA/SAV heterodimer, which recruits MST1/2 to the cell membrane; thus the LATS1/2-HM is phosphorylated.…”
Section: Hippo Signaling Pathwaymentioning
confidence: 99%
“…Meanwhile, the WW domain of the KIBRA binding to SAV results in the form of KIBRA/SAV heterodimer, which recruits MST1/2 to the cell membrane; thus the LATS1/2-HM is phosphorylated. Subsequently, phosphorylation of Ser127 in YAP interacts with 14-3-3 proteins to form a complex that remains in the cytoplasm, and the expression of target gene is also decreased [ 41 43 ]. It is reported angiomotin (AMOT) is associated with cell polarity, regulation of angiogenesis, cell migration, actin dynamics, and interaction with YAP [ 44 , 45 ].…”
Section: Hippo Signaling Pathwaymentioning
confidence: 99%